The Influence of ABS-SBK Cultural Values on Religious Moderation Among Teachers at the Syech Ahmad Khatib Islamic Boarding School - Syawaldi, Syawaldi; Hendri, Novi; Gucandra, Yudi (El-Rusyd, 2026)
This study aims to analyze the influence of the cultural values of Adat Basandi Syarak, Syarak Basandi Kitabullah (ABS-SBK) on teachers’ attitudes toward religious moderation at the Syech Ahmad Khatib Al-Minangkabauwi Tahfidz Islamic Boarding School. The study employs a quantitative approach with a causal-associative design using a field survey method. The study population and sample consisted of all 24 teachers using total sampling. The research instrument was a questionnaire with a 1-to-5 Likert scale comprising 35 items, including 20 items for the ABS-SBK cultural values variable and 15 items for the religious moderation variable. Data analysis was conducted through validity, reliability, normality, linearity, and simple linear regression tests using statistical software. The results showed that all items of variable X were valid (r = 0.419 to 0.899) and reliable, with a Cronbach’s Alpha value of 0.912. Variable Y had 13 valid items with a Cronbach’s Alpha of 0.906. The simple linear regression analysis yielded the equation Y = 8.230 + 0.658X, with a correlation coefficient R = 0.831 and a coefficient of determination R² = 0.690. This indicates that ABS-SBK cultural values have a positive and significant influence on teachers’ religious moderation, accounting for 69.0% of the variance, with a calculated t-value (7.000) greater than the critical t-value (2.074) at a significance level of 0.000 < 0.05. The dimension of internalization of traditional values is the strongest predictor in shaping teachers’ religious moderation attitudes in the Islamic Boarding School environment.